Strategi Komunikasi Guru Berbasis Media Gadget Terhadap Motivasi Belajar di Masa Covid 19 - Wahyullah Alannasir; Nurhayati Selvi; Amrullah Mahmud (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
This study aims to determine the gadget media-based teacher communication strategies during the Covid-19 period on the learning motivation of fifth grade students at SD Negeri Paccinang. This type of research is quasi-experimental research (quasi-experimental). The population in this study were 40 students of class V. The design used in this research is nonequivalent control group design. The research instruments were questionnaires, observation sheets, and documentation to test the hypothesis using the paired sample t-test. Based on the results of the study, it was found that the application of the teacher's communication strategy to fifth grade students at SD Negeri Paccinang had a positive influence on increasing student motivation. This is evidenced by the results of observations that have been made both to students and to teachers at each meeting which has increased and from the results of the average similarity test obtained a significance value of 0.000 <0.05 with tcount = 16,034 > ttable = 2,845.